PERBANDINGAN RASM MUSHAF STANDAR INDONESIA,MUSHAF PAKISTAN, DAN MUSHAF MADINAH - Hakim, Abdul (SUHUF, 2017)
Since 1984, through the decree of the Minister of Religious Affairs No. 25, Indonesia has three kinds of Standard Mushaf namely Usmani, Bahriyah and Braille. UsmaniMushaf becames standard for the publication and the circulation of the QurÃ¢â‚¬â„¢an in Indonesia. However, in fact, not all the people use Standard Usmani Mushaf. Some uses the mushafs published by India, Egypt, Saudi Arabia, Lebanon and many others. In addition to that, there is a claim in society that Medinan Mushaf is the most usmani mushaf in characteristics to be compared to others. This phenomenon, of course, tends to obscure and simplify the variety of writing in usmani rasm. This writing will compare the Standard Mushaf of Indonesia, that of Pakistan, and that of Madina with the focus of part 7, part 14 and part 24. The comparison is done on the words containing the formulation of Ã¡Â¸Â¥aÃ…Â¼f alÃ‚ÂÃ¡Â¸Â¥uruf (throwing the letter) . This descriptive analysis study shows that Indonesian Standard Usmani Mushaf in the case of rasm has similarity and closesness with that of Pakistan Mushaf by referring to the ad-DÃ„Âni narration as for the Madina Mushaf is referred to Abu DÃ„ÂwÃ…Â«d narration. Keywords: Rasm usmani, Standard Mushaf of Indonesia, Mushaf of Pakistan, Mushaf of Madinah.